Cigarette Smoking Patterns Among Racial and Ethnic Groups With Chronic Lung Diseases During the COVID-19 Pandemic - Vijaya L. Seegulam, MPH; Caretia J. Washington, BS; Parvathy P. Surendran, BPT; Alyssa M. Falise, PhD, MSPH; Diana Gomez-Manjarres, MD; Catalina Lopez-Quintero, MD, MPH, PhD (AJPM Focus)
Introduction: Chronic obstructive pulmonary disease and asthma are significant respiratory conditions that contribute to substantial morbidity and mortality globally. Chronic obstructive pulmonary disease remains the third most prevalent cause of death worldwide, with 90% of chronic obstructive pulmonary disease deaths attributed to combustible cigarette smoking. Asthma, although often less fatal, leads to considerable health burdens, particularly among marginalized populations who are at higher risk for both more severe chronic obstructive pulmonary disease and asthma outcomes. This study investigates the association between race/ethnicity and current cigarette smoking among adults diagnosed with chronic obstructive pulmonary disease and/or asthma in the U.S. before, during, and after the COVID-19 pandemic. Methods: The authors analyzed data from 10,763 adults (aged ≥40 years) with a history of chronic obstructive pulmonary disease and/or asthma surveyed in the 2019, 2021, and 2023 National Health Interview Survey. The authors estimated predicted probabilities derived from multiple logistic regression and negative binomial regression models to examine changes in (1) the prevalence of current cigarette smoking in the target population, (2) the mean number of days of cigarette smoking in the past 30 days, and (3) the mean number of cigarettes smoked in the past 30 days across racial/ethnic subgroups and prepandemic, pandemic, and postpandemic periods. Results: Current cigarette smoking was reported by about one fifth (20%) of U.S. adults diagnosed with chronic obstructive pulmonary disease and asthma. Among them, the mean number of days of cigarette smoking in the past 30 days was 27 days, and the mean number of cigarettes smoked in the past 30 days was 14. Hispanic individuals had the lowest prepandemic rates of current cigarette smoking (10.5%); however, it was the only racial/ethnic group showing a significant change during the pandemic, with rates increasing to 14.9% during the pandemic. Non-Hispanic White individuals, who showed the highest rates of current cigarette smoking (21.1%) during the pandemic, were the only racial/ethnic group showing a significant decline in the postpandemic period (19.8%). No significant changes were observed in the mean number of days or cigarettes smoked in the past 30 days, except for a marginally significant increase in cigarette consumption among non-Hispanic Black individuals. Conclusions: These analyses suggest that the pandemic had a differential impact on the rates of current smoking across racial/ethnic subgroups in adults with chronic obstructive pulmonary disease and/or asthma, with a detrimental effect in Hispanic individuals and an improvement among non-Hispanic White individuals. Given the dangers of smoking in chronic lung conditions, future research should investigate the factors behind these to develop targeted interventions.